2019
DOI: 10.18632/aging.102136
|View full text |Cite
|
Sign up to set email alerts
|

HO-1 reduces heat stress-induced apoptosis in bovine granulosa cells by suppressing oxidative stress

Abstract: Heat stress negatively affects reproduction in cattle by disrupting the normal function of ovarian granulosa cells (GCs), ultimately leading to oxidative damage and cell death via apoptosis. Heme oxygenase-1(HO-1) is a member of the heat shock protein family, which are associated with cellular antioxidant defenses and anti-apoptotic functions. Recent studies demonstrated that HO-1 is upregulated in heat-stressed cells. In the present study, we investigated the expression of HO-1 in bovine GCs transiently expos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
85
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 129 publications
(92 citation statements)
references
References 38 publications
7
85
0
Order By: Relevance
“…[ 10,11 ] Studies showed that HO‐1 was able to resist oxidative stress. [ 44 ] Activation of HO‐1 could reduce Aβ 1‐42 toxicity. [ 45,46 ] SOD catalyzes the disproportionation of superoxide anion radicals to form oxygen and hydrogen peroxide, thereby maintaining redox balance.…”
Section: Discussionmentioning
confidence: 99%
“…[ 10,11 ] Studies showed that HO‐1 was able to resist oxidative stress. [ 44 ] Activation of HO‐1 could reduce Aβ 1‐42 toxicity. [ 45,46 ] SOD catalyzes the disproportionation of superoxide anion radicals to form oxygen and hydrogen peroxide, thereby maintaining redox balance.…”
Section: Discussionmentioning
confidence: 99%
“…The effector, caspase-3, executes the final steps of apoptosis and cleaves various structural and regulatory proteins in female germ cells ( Xiong et al, 2014 ). Li et al demonstrated that oxidative stress induced bovine GC apoptosis by increasing the expression of cleaved caspase-3 and the Bax/Bcl-2 ratio as well as decreasing the expression of antioxidant enzymes (SOD2, glutathione peroxidase (GSH-Px)) ( Wang Y et al, 2019 ). In addition, excessive ROS in oocytes and GCs can induce the release of TNFα ( Kong et al, 2018 ; Miao et al, 2018 ).…”
Section: Effects Of Oxidative Stress On Apoptosis In the Ovariesmentioning
confidence: 99%
“…NRF2 is also known to be phosphorylated by activated PERK and important for cell survival during stress [37]. Previous studies also showed that the NRF2 pathway and its target genes, such as GSTD1, HO-1, and HSP70, are increased during heat stress [38][39][40][41]. To investigate the possible role of PERK in activating the NRF2 pathway during heat stress, we checked the expression levels of NRF2 target genes in Drosophila head after heat stress.…”
Section: Perk Phosphorylated Eif2α In Drosophila Neurons Upon Heat Stmentioning
confidence: 99%